2017
DOI: 10.1016/j.future.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Virtual machine cluster mobility in inter-cloud platforms

Abstract: Modern cloud computing applications developed from different interoperable services that are interfacing with each other in a loose coupling approach. This work proposes the concept of the Virtual Machine (VM) cluster migration, meaning that services could be migrated to various clouds based on different constraints such as computational resources and better economical offerings. Since cloud services are instantiated as VMs, an application can be seen as a cluster of VMs that integrate its functionality. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…In addition, cloud providers have to comply with the service level agreements (SLAs) that have been agreed upon with the customers or users. To maintain and/or improve the SLAs, researchers have proposed virtual machine (VM) migration technologies [3,4]. When there are failures or faults in the datacenter, we can migrate VMs to improve the reliability of the datacenter.…”
Section: Need Of Virtual Machine Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cloud providers have to comply with the service level agreements (SLAs) that have been agreed upon with the customers or users. To maintain and/or improve the SLAs, researchers have proposed virtual machine (VM) migration technologies [3,4]. When there are failures or faults in the datacenter, we can migrate VMs to improve the reliability of the datacenter.…”
Section: Need Of Virtual Machine Migrationmentioning
confidence: 99%
“…A focus on VM cluster migration based on SDN(Software Define Networking) architecture to reduce static end points and allow dynamic connectivity of VMs and focus on migration of VM clusters among clouds without losing network connection [3].…”
Section: Literature Surveymentioning
confidence: 99%
“…In this work we work towards these challenges, and we focus on developing an autoscaling system for microservice architectures. In the general case, an auto-scaling system would respond to current ("reactive") or predicted ("proactive") changes in workload or resource utilisation by adding or removing applications instances ("horizontal scaling") or computing resources like CPU cores ("vertical scaling") as required to meet the SLAs [6], [12], [13]. For example, "reactive" threshold-based rules are the most commonly deployed solution by Cloud Service Providers (CSPs) like AWS, Azure and Google Cloud.…”
Section: Introductionmentioning
confidence: 99%
“…The European Network and Information Security Agency (ENISA) and European Commission (EC) have perceived the merchant lock-in issue as a perhaps the best snag to big business cloud selection [5] . The audits of existing writing [6][7][8][9][10][11][12] have demonstrated that past investigations have concentrated more on interoperability and movability issues of distributed computing when lock-in is talked about. Among numerous issues being talked about are: the absence of standard interfaces and open APIs [13] , the absence of open models for VM group [14] and administration organization interfaces [15] , just as absence of open configurations for information trade.…”
Section: Introductionmentioning
confidence: 99%